2013
DOI: 10.1590/s0001-37652013005000001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet supplementation with Camu-camu (Myrciaria dubia HBK McVaugh) fruit in a rat model of diet-induced obesity

Abstract: Amazonian Camu-camu fruit (Myrciaria dubia HBK Mc Vaugh) has attracted interest from food and cosmetics industries because of its rich content of vitamin C, flavonoids and anthocyanins. The goal of this study was investigates the antiobesity action of the ingestion of the Camu-camu pulp in a rat model of diet-induced obesity. Wistar rats with obesity induced by subcutaneous injection of monosodium glutamate receiving diet ad libitum. The rats were divided in two groups: an experimental group that ingested 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 23 publications
1
24
0
12
Order By: Relevance
“…In the present study, we demonstrated that the pulp of Camu-camu reduced body weight and epididymal and visceral fat, such as reduced fat deposited in the face, heart and liver, in addition to decrease the inflammatory proteins [16]. Several experimental studies have shown that exercise combined with continued dieting results in reduced adiposity, lipid profile and reduction of biochemical parameters in rats [17][18][19].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, we demonstrated that the pulp of Camu-camu reduced body weight and epididymal and visceral fat, such as reduced fat deposited in the face, heart and liver, in addition to decrease the inflammatory proteins [16]. Several experimental studies have shown that exercise combined with continued dieting results in reduced adiposity, lipid profile and reduction of biochemical parameters in rats [17][18][19].…”
Section: Introductionsupporting
confidence: 59%
“…Researchers report results of biological assays on the action of Camu-camu (Myrciaria dubia H.B.K. McVaugh) on the reduction of lipid profile and lipid peroxidation, on triglyceride levels with decreased hypercholesterolemia in obese and diabetic rats [16,33,34] cholesterol reduction total cholesterol, LDL-c, triglycerides and modifications in the metabolic profile of adults with metabolic syndrome [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Respecto de la grasa corporal, los tejidos adiposos retroperitoneal, epididimal y visceral (mesentérica, perineal, omental) se removieron y pesaron en báscula analítica, y posteriormente se sumaron, revelando el valor total de grasa corporal de cada animal 14 . Además, se computaron el índice de adiposidad (IA) y grasa hepática conforme al método de Folch et al 15 .…”
Section: Diseño Experimental Y Dietasunclassified
“…Further, fecal cholesterol excretion was increased. In addition, assays performed by Nascimento et al [44] in a rat model of diet-induced obesity that ingested daily 25 mL of camu camu fruit pulp by 12 weeks resulted in a significant weights reduction of the fat in white adipose tissues. Triacylglycerols (↓40.6%), total cholesterol (↓39.6%), LDL cholesterol (↓2.14%), and VLDL cholesterol (↓36.4%) levels were also decreased, and HDL cholesterol (↑12.3%) increased in experimental groups.…”
Section: Antiobesity Hypolipidemic and Antihypertensive Activitiesmentioning
confidence: 99%